Exploring Cognitive Bias Influence on Investment Decisions in Indonesia: The Mediating Role of FOMO - Budiman, Johny; Ong, Teddy; Yuwono, Wisnu (Jurnal Economia, 2025)
This study investigates the impact of cognitive biases on investment decisions in Indonesia, emphasizing the mediating role of fear of missing out (FOMO). Addressing a research gap, it extends prior studies by incorporating overconfidence and risk perception alongside commonly examined biases such as loss aversion and herding. A quantitative approach was employed through a survey of retail investors, and data were analyzed using partial least squares-structural equation modeling (PLS-SEM) via SmartPLS. The findings reveal that herding exerts a significant influence on investment decisions, whereas loss aversion, overconfidence, and risk perception show no direct effect. Notably, FOMO mediates the relationship between loss aversion and investment decisions, though herding remains the most dominant factor. These results suggest that while Indonesian investors demonstrate rational tendencies, susceptibility to social dynamics and behavioral triggers persists. The study contributes to behavioral finance literature and offers practical insights for mitigating bias-driven investment risks.